1998
DOI: 10.1046/j.1365-2427.1998.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Light availability as a possible regulator of cyanobacteria species composition in a shallow subtropical lake

Abstract: 1. Variations in the relative biovolumes of dominant cyanobacterial taxa were evaluated in the context of environmental conditions using canonical correlation analysis (CCorrA) and Redundancy Analysis (RDA). The objective was to test a conceptual model in which underwater irradiance determines dominance by bloom‐forming (high light adapted) or non‐blooming (low light adapted) taxa. 2. The data set consisted of 404 contiguous observations, collected over a 3‐year period at eight pelagic sites, in shallow Lake O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
88
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 30 publications
12
88
0
1
Order By: Relevance
“…Cyanobacterial abundance decreased from 2007 to 2010 after the applied EEM contributed to decrease TP concentrations and to reduce underwater light intensity. As already observed by Havens et al (1998) in a shallow sub-tropical lake, phytoplankton biomass, especially that of high-light adapted, bloomforming taxa such as the S-strategist Microcystis spp. strongly decreased when water transparency decreased due to the shading effect of floating beds.…”
Section: Discussionsupporting
confidence: 70%
“…Cyanobacterial abundance decreased from 2007 to 2010 after the applied EEM contributed to decrease TP concentrations and to reduce underwater light intensity. As already observed by Havens et al (1998) in a shallow sub-tropical lake, phytoplankton biomass, especially that of high-light adapted, bloomforming taxa such as the S-strategist Microcystis spp. strongly decreased when water transparency decreased due to the shading effect of floating beds.…”
Section: Discussionsupporting
confidence: 70%
“…We found 15 N depletion in several eutrophic lakes known to have nitrogen-fixing cyanobacterial blooms (Chapman and Schelske, 1997;Havens et al, 1998;Gu et al, 2006). Previous studies have found low d 15 N POM and the presence of nitrogen-fixing cyanobacteria in eutrophic lakes (Gu and Alexander, 1993;Lehmann et al, 2004).…”
Section: Discussionsupporting
confidence: 47%
“…As mentioned, an inverse relationship between cumulative IR and chlorophyll a concentration could be seen, with factors such as shading, period of exposure and erosion likely affecting chlorophyll a concentration. In addition, these comparisons between IR and chlorophyll a concentration suggest that low-light adaptation of photoautotrophic microorganisms, shown as important in shallow, turbid lacustrine ecosystems (Scheffer et al, 1997;Havens et al, 1998), may be a further factor controlling photosynthesis and thus bioaggregation. Furthermore, given that carbohydrate concentrations were found to increase up-glacier, it could be that radiation stresses necessitate microbial carbohydrate production (Chen et al, 2009) to provide a matrix for UV-protective mycosporine-like amino acids (Quesada and Vincent, 1997), in addition to the potential for cryoprotection and nutrient scavenging roles.…”
Section: H J Langford Et Al: Spatial Study Of Cryoconite Aggregatimentioning
confidence: 87%